Using ecological momentary assessment to enhance irritability phenotyping in a transdiagnostic sample of youth. (December 2021) - Naim, Reut; Smith, Ashley; Chue, Amanda; Grassie, Hannah; Linke, Julia; Dombek, Kelly; Shaughnessy, Shannon; McNeil, Cheri; Cardinale, Elise; Agorsor, Courtney; Cardenas, Sofia; Brooks, Julia; et al.
Abstract: Irritability is a transdiagnostic symptom dimension in developmental psychopathology, closely related to the Research Domain Criteria (RDoC) construct of frustrative nonreward. Consistent with the RDoC framework and calls for transdiagnostic, developmentally-sensitive assessment methods, we report data from a smartphone-based, naturalistic ecological momentary assessment (EMA) study of irritability. We assessed 109 children and adolescents ( M age = 12.55 years; 75.20% male) encompassing several diagnostic groups – disruptive mood dysregulation disorder (DMDD), attention-deficit/hyperactivity disorder (ADHD), anxiety disorders (ANX), healthy volunteers (HV). The participants rated symptoms three times per day for 1 week. Compliance with the EMA protocol was high. As tested using multilevel modeling, EMA ratings of irritability were strongly and consistently associated with in-clinic, gold-standard measures of irritability. Further, EMA ratings of irritability were significantly related to subjective frustration during a laboratory task eliciting frustrative nonreward. Irritability levels exhibited an expected graduated pattern across diagnostic groups, and the different EMA items measuring irritability were significantly associated with one another within all groups, supporting the transdiagnostic phenomenology of irritability. Additional analyses utilized EMA ratings of anxiety as a comparison with respect to convergent validity and transdiagnostic phenomenology. The results support new measurement tools that can be used in future studies of irritability and frustrative nonreward.